Chemosensory enrichment as a simple and effective way to improve the welfare of captive lizards. (2nd August 2018) - Londoño, Claudia; Bartolomé, Alicia; Carazo, Pau; Font, Enrique
Abstract: Environmental enrichment has proven to be a useful and effective welfare tool in order to evaluate and enhance the well‐being of captive animals, but only when it is based on detailed knowledge of each species' natural behaviour. Chemoreception is fundamental to many aspects of reptilian biology; however, sensory enrichment with chemical stimuli has rarely been applied to reptiles. In this study, we evaluate the use of chemosensory enrichment as a method to enhance the welfare of Podarcis liolepis . For seven weeks, we exposed field‐caught males to scents from donor conspecific males collected on pieces of filter paper (i.e., "enriched" group, n  = 18), and compared their behaviour to that of control males provided with unscented pieces of filter paper ( n  = 18). We measured the occurrence of normal (e.g., locomotion) and abnormal (escape attempts) behaviours each day for three weeks. In addition, we conducted two exploration tests and a visual barrier test. Compared to controls, enriched lizards showed a consistent long‐term decrease (29%–38%) in the occurrence of escape attempts. During exploration tests, enriched lizards spent less time performing escape attempts and devoted more time to perching than controls. As expected, both control and enriched lizards showed a reduction of time in locomotion and an increase in the time spent perching between the first and second exploration test, but these changes were significantly more pronounced for enriched animals. Taken together, our results suggest improved welfare of enriched animals, as they spent less time engaging in abnormal behaviours, more time in normal behaviours, and showed signs of faster habituation to a novel environment. Chemosensory enrichment is a relatively simple enrichment strategy that could potentially be applied to improve the welfare of a wide range of captive lizards, and reptiles at large.